A performance profile of a top Bosnian Herzegovinian judo athlete Larisa Ceric - Kajmovic, H.; Becic, F.; Lampe, N.; Miletic, T. (The Arts and Sciences of Judo, 2025)
A significant number of women have made an invaluable contribution to the promotion and development of judo worldwide through their achievements. One such athlete is elite competitor Larisa Èeriæ, a three-time Olympian and a multiple medallist in world, European, Mediterranean, university, Balkan, and national championships. She has left a profound mark on Bosnian-Herzegovinian judo.